2000
DOI: 10.1038/labinvest.3780009
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity on Chromosome 10 Is More Extensive in Primary (De Novo) Than in Secondary Glioblastomas

Abstract: SUMMARY:Glioblastomas develop de novo (primary glioblastomas) or through progression from low-grade or anaplastic astrocytoma (secondary glioblastomas). There is increasing evidence that these glioblastoma subtypes develop through different genetic pathways. Primary glioblastomas are characterized by EGFR and MDM2 amplification/overexpression, PTEN mutations, and p16 deletions, whereas secondary glioblastomas frequently contain p53 mutations. Loss of heterozygosity (LOH) on chromosome 10 (LOH#10) is the most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 40 publications
3
110
1
4
Order By: Relevance
“…Recent evidence suggests that complete losses of one copy of chromosome 10 are more frequent in primary GBM and partial losses in secondary GBM. 2 More often deletions affect the long arm of chromosome 10 but in a large fraction of patients they are also present on the short arm. 3 A comparable frequency of deletions on 10p has been found in prostate cancer.…”
Section: Dear Sirmentioning
confidence: 99%
“…Recent evidence suggests that complete losses of one copy of chromosome 10 are more frequent in primary GBM and partial losses in secondary GBM. 2 More often deletions affect the long arm of chromosome 10 but in a large fraction of patients they are also present on the short arm. 3 A comparable frequency of deletions on 10p has been found in prostate cancer.…”
Section: Dear Sirmentioning
confidence: 99%
“…DNA was extracted from paraffin sections, as described previously, to be used for microsatellite analysis. 3,6 Control genomic DNA was extracted from separate tissue blocks not involved with the tumor.…”
Section: Tumor Samples and Dna Extractionmentioning
confidence: 99%
“…Another type of glioblastoma, the so-called secondary glioblastoma, progressively develops more slowly from low-grade diffuse (WHO grade II) or anaplastic astrocytoma (WHO grade III). 1 Recent genetic analyses have shown that these glioblastoma subtypes develop through different genetic pathways; 2-4 primary glioblastomas occur in older patients characterized by EGFR amplification/overexpression, PTEN mutation, homozygous p16 INK4a deletion, and loss of heterozygosity (LOH) throughout chromosome 10, 3,5,6 while secondary glioblastomas develop in younger patients and typically show frequent p53 mutations, LOH preferentially on chromosomes 10q and 19q, 3,[5][6][7] and promoter methylation of the RB1 gene. 8 LOH on 22q seems to be of interest, since this allelic loss is a common event in gliomas, occurring with a frequency varying between 11 and 39%.…”
mentioning
confidence: 99%
“…Recent studies have shown that these glioblastoma subtypes develop through different genetic pathways Kleihues and Ohgaki, 1999;Lang et al, 1994;Tohma et al, 1998;von Deimling et al, 1992;Watanabe et al, 1996). Primary glioblastomas are characterized by EGFR amplification/overexpression, PTEN mutations, p16 INK4a homozygous deletion, and loss of heterozygosity (LOH) on chromosomes 10p and 10q Fujisawa et al, 2000;Kleihues and Ohgaki, 1999;Tohma et al, 1998;Watanabe et al, 1996), whereas secondary glioblastomas contain frequent p53 mutations and show LOH preferentially on chromosomes 19q and 10q (Fujisawa et al, 2000;Kleihues and Ohgaki, 1999;Nakamura et al, 2000b;Watanabe et al, 1996Watanabe et al, , 1997.…”
mentioning
confidence: 99%